Explaining the Challenges of the Iranian Health System in the Face of Future Aging: Qualitative Study - Rahele Samouei; Mahmoud Keyvanara (University of Social Welfare & Rehabilitation Sciences, 2022)
Objectives: The goals of global growth of the elderly population and ensuring the health of the elderly is a global event and one of the most important challenges of the health system of countries, especially developing countries and Iran; In this regard, the study was conducted to explain the challenges of the Iranian health system in the face of future aging. Methods & Materials: The study was qualitative content analysis. A total of 29 experts from various disciplines including geriatrics, psychology, social medicine, nursing, medicine, health and social welfare, health policy, health care management and health economics participated in the study. The data obtained from the semi-structured interview were classified by the content analysis method. Lincoln and Guba criteria were used to assess validity. Results: In identifying the challenges of the Iranian health system in the face of future aging Two general concepts including policy challenges, including barriers related to planning and implementation, financial barriers, vision barriers, therapeutic barriers, Health barriers, educational barriers and individual social challenges were identified, including cultural value barriers, and individual barriers. Conclusion: The frequency and variety of challenges of increasing the elderly population in the country according to the findings of the study indicate the critical state of the health system in the near future. Identifying these challenges can be used by policymakers and planners for any planning and action.